Understanding forest landscape dynamics - Jong, W. de (ITTO, 2005)
This chapter is based on the premise that the forest landscape we want to manage and restore is the product of dynamic forces operating as direct or indirect causes of change. The chapter highlights the importance of understanding and addressing the forces responsible for landscape change to ensure that restoration efforts are successful. Essentially, landscape dynamics include changes in the composition of the landscape (that is, the make-up of the various landscape components such as forest land, agricultural land, or housing) and changes in the condition of individual components (such as conversion of agricultural land from grazing to crop production).